Air quality integrated assessment modelling in the context of EU policy: A way forward. Issue 65 (November 2016) - Viaene, P.; Belis, C.A.; Blond, N.; Bouland, C.; Juda-Rezler, K.; Karvosenoja, N.; Martilli, A.; Miranda, A.; Pisoni, E.; Volta, M.
Highlights: Guidance is provided for the integrated assessment (IAM) of local air quality. IAM components can be mapped to the elements of the DPSIR scheme. A standard solution for IAM does not exist. The level of detail of IAM components should ensure that the IAM is 'fit-for-purpose'. Abstract: In the EU-FP7 project APPRAISAL the current practice for integrated assessment modelling (IAM) of air quality in the EU was reviewed, limitations were identified and guidance for improvements was provided. In this article we present the guidance proposed by APPRAISAL. This guidance takes into account that a single IAM solution does not exist but that the different elements of the IAM methodology can be addressed in more or less detail taking into account the available data, the regional/local specificities, the financial resources and the actual purpose of the assessment.